Optimizing Learning Through Contextual SDGs-Based Card Match Index Media - Listiadi, Agung (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Human resources and employment are issues related to achieving two of the Sustainable Development Goals (SDGs): SDGs 4 and 8, which focus on sustainable education and decent work, respectively. The purpose of this study is to create contextual stimulation that can address various learning barriers in accounting subjects. The implementation of this index-card match model aims to foster group cooperation, mutual appreciation, and learning correction. This research employs a statistical method, specifically a combination of the paired T-test and the 4-D Thiagarajan model. The instrument for collecting research data utilizes an open questionnaire validated through expert review. The research results indicate that, overall, students exhibit high motivation towards the accounting material studied in class when using contextual index-card matching, and that there is a significant difference between using a card-match index and not using one. The findings reveal that learning through the index-card match-type active learning method positively affects learning activities and achievement compared with the talking stick method. This suggests that the index-card match-type active learning model offers students opportunities to improve their learning outcomes.